2019
DOI: 10.1556/004.2019.055
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the red fox as a natural reservoir of intestinal zoonoses in Vojvodina, Serbia

Abstract: In the present study, 223 foxes were collected from various localities in the northern part of the Republic of Serbia (Vojvodina province) and examined for intestinal helminths. Among the examined foxes 178 (79.8%) were infected. The most frequently identified parasites were Mesocestoides spp. (49.3%) and Toxascaris leonina (36.3%). The parasite with the lowest prevalence was Pterygodermatites affinis (0.9%), and this is the first confirmed finding in Serbia. The other recovered species were Alaria alata (25.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
3
10
1
3
Order By: Relevance
“…This finding was the first report of E. multilocularis in jackals on the European continent (Sz ell et al, 2013). In the current study, the prevalence of E. multilocularis was 14.1%, with all infected jackals originating from the Srem region, which reflects the infection seen in red foxes as reported by Miljevi c et al (2019). To explain the presence of the parasite in this part of Vojvodina, the authors hypothesise that infection can freely spread via mobile wildlife between Croatia and Srem, which are geographically continuous; the river Danube would act as a barrier preventing the disease from spreading further north into Ba cka and Banat.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This finding was the first report of E. multilocularis in jackals on the European continent (Sz ell et al, 2013). In the current study, the prevalence of E. multilocularis was 14.1%, with all infected jackals originating from the Srem region, which reflects the infection seen in red foxes as reported by Miljevi c et al (2019). To explain the presence of the parasite in this part of Vojvodina, the authors hypothesise that infection can freely spread via mobile wildlife between Croatia and Srem, which are geographically continuous; the river Danube would act as a barrier preventing the disease from spreading further north into Ba cka and Banat.…”
Section: Discussionsupporting
confidence: 74%
“…The present results demonstrate that golden jackals from Vojvodina are hosts of eight intestinal helminth species. A previous study found a similar parasite fauna in red foxes from the same sampling area in Vojvodina examined between 2015 and 2018 (Miljevi c et al, 2019); however, in the present study, Pterygodermatites affinis was not recorded in jackals. These findings indicate that identical ecological conditions and physical environment may have a greater impact on the presence of certain parasite species, regardless of their definitive host.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The trematodes of the Alaria genus are parasites of many wild and domestic carnivores, mainly foxes, wolves, raccoons, dogs and cats (3,10,12,16,18,34,37). The parasite has a complex life cycle with two intermediate hosts.…”
mentioning
confidence: 99%